Correlation between dental anxiety and salivary pH prior to the tooth extraction - Stefani, Stacia; Tjahajawati, Sri (Universitas Padjadjaran, 2014)
Introduction: Dental anxiety can be one of inhibiting faktor in dental care that must be immediately detected and handled by dentists. Dental anxiety can cause physiological changes such as reduced salivary secretion that can cause reduced salivary pH. The aim for this study is to find correlation between dental anxiety and salivary pH, so that salivary pH can be one of indicator of dental axiety. Methods: This descriptive analytic study used consecutive sampling technique and was analyzed by Rank Spearman correlation test. Dental anxiety and salivary pH was measured in 53 respondents before tooth extraction using Corah’s Dental Anxiety Scale and pH paper. Results: The results from this study show that respondents with dental anxiety have lower average salivary pH. Statistic calculation using Rank Spearman correlation test with α =5%, shows cofficient correlation rs =0.438 with t = 3.479 and ta/2(n-2) = 2.008. Conclusion: The conclusion from this study shows that there is a correlation between dental anxiety and salivary pH before tooth extraction.